Anterior segment morphometric changes and intraocular pressure lowering after phacoemulsification with intraocular lens implantation for the prevention of pseudoexfoliative glaucoma in patients with pseudoexfoliation syndrome (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To assess intraocular pressure (IOP)-lowering and morphometric changes in the anterior segment after phacoemulsification with intraocular lens (IOL) implantation for the prevention of pseudoexfoliative glaucoma in eyes with pseudoexfoliation syndrome (PEX).Material and Methods: Four hundred and eighty eight patients (625 eyes; age, 49 to 79 years) with evidence of senile cataract associated with PEX (group 1) were included in the study. The control group (group 2) included 122 patients (188 eyes) with confirmed senile cataract without PEX. All patients had phacoemulsification with IOL implantation. Goldmann applanation IOP was measured preoperatively and 1 week and 1 and 3 months postoperatively.Results: In eyes of patients with cataract associated with PEX, the anterior chamber appeared to be 0.3 mm shallower, on average, and the anteroposterior axis of the lens, 1.02 mm longer, on average than those in eyes of patients with cataract without PEX. In addition, in eyes of the former patients, the anterior chamber showed a 30% increase in depth after cataract surgery compared to baseline. We also determined IOP values in eyes of patients with PEX and those without PEX before and after phacoemulsification with IOL implantation. Eyes of the latter patients showed a gradual 1.4-mm Hg reduction in IOP over 3 months after surgery, whereas eyes of the former patients showed an insubstantial IOP increase at 1 week, and a significant 3-mm Hg IOP lowering at 3 months after surgery.Conclusion: In eyes with PEX, cataract was accompanied by morphometric anterior segment changes, with 0.3-mm greater anterior chamber shallowing and 1.02-mm greater elongation of the anteroposterior axis of the lens, compared to eyes without PEX. At 3 months after phacoemulsification with IOL implantation, eyes with PEX showed a percentage IOP reduction of 16.9%.
Keywords: cataract; intraocular pressure; neovascular glaucoma; pseudoexfoliation syndrome; phacoemulsification; glaucoma